(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article explores the integration of 3D technologies and the Internet of Things (IoT) into the field of handicrafts. The main objective is to modernize traditional production processes, improve product quality, enhance production efficiency, and ensure global competitiveness through proposed recommendations and solutions.